2011
DOI: 10.1161/circheartfailure.111.962571
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorenal Actions of TRV120027, a Novel ß-Arrestin–Biased Ligand at the Angiotensin II Type I Receptor, in Healthy and Heart Failure Canines

Abstract: Background-The angiotensin II type 1 receptor (AT1R) plays a key role in regulating cardiorenal function. Classic "unbiased" AT1R antagonists block receptor coupling to both G ␣q and ß-arrestin-mediated signals, which desensitize G-protein signaling as well as transduce G-protein-independent signals. TRV120027 is a novel ß-arrestin-biased AT1R ligand, which engages ß-arrestins while blocking G-protein signaling. At the AT1R, TRV120027 can inhibit angiotensin II-mediated vasoconstriction, whereas, through ß-arr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
105
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(112 citation statements)
references
References 34 publications
5
105
0
2
Order By: Relevance
“…promote cardiomyocyte contraction along with activation of antiapoptotic signaling (37,38). To date, a comparable ligand has not been reported for β-adrenergic receptors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…promote cardiomyocyte contraction along with activation of antiapoptotic signaling (37,38). To date, a comparable ligand has not been reported for β-adrenergic receptors.…”
Section: Discussionmentioning
confidence: 99%
“…As G-protein-dependent signaling has been attributed to cardiomyocyte death, the use of a β-arrestin-biased agonist could be an advantageous therapeutic approach (34). Beyond its inability to activate G-protein signaling, evidence has suggested that β-arrestinbiased signaling promotes cardiomyocyte survival signaling along with induction of cardiomyocyte contractility (3,(35)(36)(37)(38). Indeed, a β-arrestin-biased agonist for the angiotensin II type 1A receptor (AT1 A R), TRV027, has demonstrated the ability to promote β-arrestin-dependent cardiac contraction in vivo and is currently in clinical trials for the treatment of heart failure (37, 38).…”
Section: Icl1-9mentioning
confidence: 99%
“…Stimulation by Ang II or [Sar 1 , Ile 4 , Ile 8 ] Ang II of AT1a receptor led to positive inotropic and lusitropic responses in wild-type cardiomyocytes, whereas this response was abolished in ␤-arrestin 2 knock-out cardiomyocytes (61). The therapeutic potential of such compounds has been illustrated by the development of TR120027, a AT1a receptor ␤-arrestin-biased agonist, which improved cardiac performance and had cardioprotective activity by blocking the G protein-mediated vasoconstriction while increasing the cardiac contractility through ␤-arrestin signaling (62,63). The activation of ApelinR ␤-arrestin-mediated signaling could have also a biological role because only apelin fragments that fully activate ␤-arrestin induced a decrease in arterial BP (14).…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, TRV120027 targets the AT1R in such a way that blocks of the G-protein mediated adverse effects of Ang II while simultaneously unmasks beneficial pharmacology mediated by beta-arrestin. Its benefits to heart and kidney were already clearly demonstrated in animal models by us and others [10][11][12].…”
mentioning
confidence: 80%